Mechanical properties of austenitic stainless steel with high niobium contents. Issue 13 (1st September 2016) - Okayasu, M.; Wu, S.; Noda, K.; Lin, D.-Y.; Yang, S.-M.
Abstract : To better understand the influence of the microstructural characteristics on the mechanical properties of Fe-Cr22 -Ni25 -Nb x austenitic stainless steel (ASS-Nb x ), the mechanical properties were investigated. Nb addition was conducted with four different amounts: 0, 0.29, 0.58 and 0.86%. With the increasing Nb content, the mean grain size for the Fe-Cr-Ni-based alloys decreased, while the size of Nb precipitate increased. Owing to the different microstructural characteristics, their mechanical properties were altered. The highest tensile strength was obtained for ASS-Nb0.29 alloy. However, with the increasing Nb content in ASS-Nb0.29–0.86 alloys, the tensile strength decreases despite the grain refinement. The mechanical properties of the ASS-Nb alloys were influenced by the Nb precipitation hardening and the grain boundary cohesive strength, arising from the size of Nb precipitations.